Structural Behaviour Of Precast Concrete Wall As Industrialized Building System Subjected To Axial Load: A Review - CHAI, CHUAN ZHI; MOHAMAD, NORIDAH (Recent Trends in Civil Engineering and Built Environment, 2022)
Industrialized Building System (IBS) is a building skill that involves the manufacturing of components such as slabs, columns and walls in a factory and installed at the construction site. Precast concrete wall has more advantages compared to in-situ concrete because it has shorter building time and lower overall cost. Precast solid wall is made with conventional concrete and without insulating materials, but precast sandwich wall is produced with self-compacting concrete and foam concrete containing a layer of insulation. This study focuses on the structural behavior of both types of walls and comparison were conducted on which wall has greater structural performance. The methodology of this analysis consists of two steps in which all the data derived from the previous experimental work were collected and compared. The analysis was done from numerous papers and journals by examining the axial strength, crack pattern and load-deflection profile.  After the review from the previous studies, it can be concluded that precast foamed concrete sandwich wall has a higher structural performance than precast solid wall.